Entre lo simbólico y lo real: las leyes anticlericales de 1884 en Costa Rica - Solano Muñoz, Edgar (1994)
A study of the impact of anti-Church legislation adopted in 1884 in Costa Rica, as regards the activities of Costa Rican clergy. The article focuses on the secularization of cemeteries, the prohibition of religious celebrations outside the churches, and an analysis of the financial situation of the Church.